Respon Pertumbuhan dan Produksi Terong Ungu Terhadap Pemberian Kotoran Hewan Sapi dan NPK 16-16-16: Response of Growth and Yield of Purple Eggplant to Cattle Manure and NPK 16-16-16 Application - Media Farica Diva; Rr. Djarwatiningsih Djarwatiningsih; Felisitas Deru Dewanti (Agrocentrum, 2026)
This study looked at how important growth and production characteristics of purple eggplant (Solanum melongena L.) were affected by cow dung and NPK 16-16-16 fertilizer, both separately and in combination. Plant height, flowering time, total number of fruits per plant, total fruit weight, fruit length, and fruit diameter were the main emphasis of the study. A factorial design was employed in the experiment, and analysis of variance was utilized to examine the results. The interaction between NPK 16-16-16 and cow dung did not significantly affect any of the characteristics that were examined, according to the results. Plant height, flowering period, fruit quantity, weight, length, and diameter were all not substantially impacted by cattle dung alone. Better responses were obtained in a number of yield components by NPK 16-16-16, although not all results were statistically significant. In general, single factors particularly NPK have a greater impact on plant growth and yield than treatment interactions.